Pixantrone for the treatment of adult patients with relapsed or refractory aggressive non-Hodgkin B-cell lymphomas - Volpetti, Stefano (Dove Medical Press, 2014)
Treatment of patients with relapsed or refractory aggressive non-Hodgkin B-cell lymphoma remains an unmet clinical need, and the progressive myocardial toxicity related to cumulative, dose-dependent damage induced by anthracyclines represents a tricky issue in the planning of therapy. Pixantrone is a promising aza-anthracenedione with reduced cardiotoxicity and significant antineoplastic activity, and has been investigated in solid and hematologic tumors in several Phase I, II, and III trials. The aim of this review is to summarize the data reported so far on pixantrone as a salvage therapy in relapsed/refractory non-Hodgkin B-cell lymphoma.